Ligneous conjunctivitis associated with type I plasminogen deficiency: A rare case. Issue 5 (September 2022) - Dimopoulos, Dimitris; Zacharioudakis, Andreas; Kazamias, Georgios; Danilatou, Viasiliki; Katerini, Dimitra; Nodarakis, Michael; Koutentaki, Maria Eleni; Koutentakis, Pavlos
Ligneous conjunctivitis is a rare form of chronic, recurrent conjunctivitis characterized by wood-like, fibrinous pseudomembranes, which may be associated with systemic disease manifestations. It has been associated with congenital plasminogen (PLG) deficiency that is inherited with an autosomal recessive pattern due to mutations in the PLG gene and a variety of other genes, leading to disturbed wound healing. In this case report, we present the clinical, laboratory, and histopathological findings of a 36-year-old female patient who presented at the ophthalmology department with complaints of redness, irritation for the previous few weeks, and appearance of membranous lesions mainly on the tarsal conjunctivae. During biomicroscopic examination we found thick, yellowish-white pseudomembranes, and conjunctival proliferation with ligneous induration on the conjunctiva, located on the upper eyelids. Histopathological evaluations showed up ligneous conjunctivitis and laboratory evaluation confirmed a severe plasminogen deficiency (PLG < 2%). The patient was treated with topical fresh frozen plasma (FFP), topical steroids, heparin eye drops, and artificial tear drops daily, without systemic therapy.